2020
DOI: 10.1002/admi.201902080
|View full text |Cite
|
Sign up to set email alerts
|

Chlorosome‐Like Molecular Aggregation of Chlorophyll Derivative on Ti3C2Tx MXene Nanosheets for Efficient Noble Metal‐Free Photocatalytic Hydrogen Evolution

Abstract: such as global warming and climate changes. [1][2][3][4] Solar energy is clean and abundant, for example, nearly four million exajoules (4 × 10 18 J) of solar energy reaches the earth annually. [1,5] Conversion of solar energy into chemical energy through photocatalytic decomposition of water to produce hydrogen is one of the suitable approaches to utilize solar energy. [6][7][8][9][10] The different types of fundamental photocatalytic reactions include i) semiconductor-based photocatalysis, ii) dye-sensitized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 51 publications
1
32
0
Order By: Relevance
“…In contrast, incorporation of chlorophyll aggregates in the photocatalytic H 2 evolution systems is of great potential. We recently demonstrated the fabrication of organic–inorganic composites by deposition of supramolecular aggregates of ZnChl‐9 on the surface of Ti 3 C 2 T x MXene with 2D accordion‐like morphology (Figure e) . MXenes are a new family of 2D nanostructured materials, which have attracted more and more attention since 2011 due to their unique optoelectronic properties with tunable surface termination .…”
Section: Application Of Chlorophyll Derivatives As Photocatalyst For mentioning
confidence: 99%
“…In contrast, incorporation of chlorophyll aggregates in the photocatalytic H 2 evolution systems is of great potential. We recently demonstrated the fabrication of organic–inorganic composites by deposition of supramolecular aggregates of ZnChl‐9 on the surface of Ti 3 C 2 T x MXene with 2D accordion‐like morphology (Figure e) . MXenes are a new family of 2D nanostructured materials, which have attracted more and more attention since 2011 due to their unique optoelectronic properties with tunable surface termination .…”
Section: Application Of Chlorophyll Derivatives As Photocatalyst For mentioning
confidence: 99%
“…It was shown that they could form aggregates to efficiently capture sunlight and transport charge compared with their monomers. Such properties of Chl derivatives have been applied in solar cells, [11–13] energy storage, [14] and photocatalytic hydrogen evolution [15] . Compared with other photocatalysts that use synthetic photoactive materials, Chls are cost‐effective, environmentally friendly, easy to be disposed of, abundant, and nonpoisonous natural pigments.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous investigation, we combined zinc methyl 3‐devinyl‐3‐hydroxymethyl‐pyropheophorbide a (Chl‐1; Figure 1) with Ti 3 C 2 T x MXene for the HER, and we proved that hydrogen was generated through exciton transfer in Chl‐1 aggregates followed by charge transfer to Ti 3 C 2 T x [15] . However, the performance of this system was still insufficient and required further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to MoS2 and graphene, MXene research is still in the early stages. Unlike MoS2 and graphene, MXenes do not have stacked structure that can be peeled directly, and most MXene syntheses are based on the structure removal of MAX phases [86][87][88][89].…”
Section: Two-dimensional Materials For Hermentioning
confidence: 99%